ACCOUNTING IN ISLAMIC SOCIETIES: AL BAQARAH 282-283 - Dzikriya Syukriyana; Noer Sasongko; Rina Trisnawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Accounting as a part of social sciences cannot separated from the ethical, moral, and cultural values surrounding it. The arrival of Islam through the Qur'an provides the guidance of every life’s aspects, including accounting. Accounting explicitly explained in Al Baqarah 282-283 and implicitly explained in various study of trading, zakah and usury. This is a qualitative study. The data collected by interviews, observations and literature studies. Data was analyzed and presented in the Miles and Huberman Models. The results of this study indicate that Al Baqarah 282-283 is the main reference of Islamic Accounting that explains the accounting hierarchy. Al Baqarah 282 explains four accounting process, including identifying, recording, communicating and witnessing. This verse also explains the qualitative characteristics for accountants and financial information.